OPTIMASI PERTUMBUHAN CAULERPA SP YANG DIBUDIDAYAKAN DENGAN KEDALAMAN YANG BERBEDA DI PERAIRAN LAGURUDA KABUPATEN TAKALAR - Darmawati Darmawati; Rahmi Rahmi; Eko Aprilyanto Jayadi (Universitas Muhammadiyah Makassar, 2016)
The study aims to determine the effect of planting depth of seaweed (Caulerpa sp) is different to growth, as well as the depth of planting is best for the growth of seaweed Caulerpa sp. The experimental design of this study was completely randomized design (CRD) with 3 treatments ie different planting depths are: 50 cm, 100 cm and 150 cm, each treatment was repeated 3 test kali.Parameter absolute growth and daily growth rate is using ANOVA and followed by LSD test. Based on these results, value - average absolute growth (PM) was obtained at a depth of 50 cm is (197.5 g) followed by a depth of 100 cm (177.5 g) and the lowest at a depth of 150 cm (114.3 g). Results of water quality measurements at the site of the research is still in the ideal conditions for the growth of Caulerpa sp.